Regulacijske začasne odredbe - Pogorelčnik Vogrinc, Neža (Zbornik znanstvenih razprav (Pravna fakulteta. 1991), 2013)
Before the decision of Constitutional court of Republic Slovenia Up-275/97 the only purpose of interlocutory injunctions was to protect future enforcement (so called security interlocutory injunctions). To protect an effectiveness of constitutional right to judicial protection the Constitutional court allowed interlocutory injunctions regulating a legal relationship that is in dispute even during the court proceeding and therefore prior to the final judgment (so called regulatory interlocutory injunctions). But a possibility of issuing these without their normative regulation induced in case-law a lot of questions. The article tries to answer some of them with studying relevant case-law and legal theory.
Keywords: dolgovi; terjatve; izvršba; zavarovanje; izvšilni postopek